Filament formation via collision-induced magnetic reconnection - formation of a star cluster - Kong, Shuo; Whitworth, David J.; Smith, Rowan J; Hamden, Erika T (Monthly notices of the Royal Astronomical Society, 2022)
A collision-induced magnetic reconnection (CMR) mechanism was recently proposed to explain the formation of a filament in the Orion A molecular cloud. In this mechanism, a collision between two clouds with antiparallel magnetic fields produces a dense filament due to the magnetic tension of the reconnected fields. The filament contains fiber-like sub-structures and is confined by a helical magnetic field. To show whether the dense filament is capable of forming stars, we use the arepo code with sink particles to model star formation following the formation of the CMR-filament. First, the CMR-filament formation is confirmed with arepo. Secondly, the filament is able to form a star cluster after it collapses along its main axis. Compared to the control model without magnetic fields, the CMR model shows two distinctive features. First, the CMR-cluster is confined to a factor of ∼4 smaller volume. The confinement is due to the combination of the helical field and gravity. Secondly, the CMR model has a factor of ∼2 lower star formation rate. The slower star formation is again due to the surface helical field that hinders gas inflow from larger scales. Mass is only supplied to the accreting cluster through streamers.
Gesehen am 18.01.2023